Neuronal activity drives IGF2 expression from pericytes to form long-term memory - Pandey, Kiran; Bessières, Benjamin; Sheng, Susan L.; Taranda, Julian; Osten, Pavel; Sandovici, Ionel; Constancia, Miguel; Alberini, Cristina M. (Neuron, 2023)
Investigations of memory mechanisms have been, thus far, neuron centric, despite the brain comprising diverse cell types. Using rats and mice, we assessed the cell-type-specific contribution of hippocampal insulin-like growth factor 2 (IGF2), a polypeptide regulated by learning and required for long-term memory formation. The highest level of hippocampal IGF2 was detected in pericytes, the multi-functional mural cells of the microvessels that regulate blood flow, vessel formation, the blood-brain barrier, and immune cell entry into the central nervous system. Learning significantly increased pericytic Igf2 expression in the hippocampus, particularly in the highly vascularized stratum lacunosum moleculare and stratum moleculare layers of the dentate gyrus. Igf2 increases required neuronal activity. Regulated hippocampal Igf2 knockout in pericytes, but not in fibroblasts or neurons, impaired long-term memories and blunted the learning-dependent increase of neuronal immediate early genes (IEGs). Thus, neuronal activity-driven signaling from pericytes to neurons via IGF2 is essential for long-term memory.